On the life and habits of gas-core slugs: characterisation of an intermittent horizontal two-phase flow - Arellano, Yessica; Hunt, Andrew; Haas, Olivier; Ma, Lu (Journal of natural gas science and engineering, 2020)
Slugs are intermittent structures observed in horizontal co-current gas-liquid two-phase flow. Published data examining horizontal flow indicate the existence of intermittent sub-flow patterns. There is limited work performed on the study of this sub-categorisation. This paper presents a method, exploiting non-intrusive Electrical Capacitance Tomography (ECT) measurements, to assess and to characterise the spatial and temporal features of horizontal gas-oil flow. A logic-based algorithm is proposed to automatically identify and classify flow regimes. This algorithm uses the spatial distribution of the phases, based on measurements of the intrinsic dielectric properties of the fluids. The measurements were performed at the NEL UK national standard multiphase flow loop using a high-speed dual-plane ECT sensor array. The ECT measurements identified intermittent liquid structures with a sustained gas-core in the central region of the pipe cross-section with outer features analogous to those of liquid slugs. Assessment of the frequency and time span of the periodic structures showed that gas-core slugs are, typically, shorter than full slug structures but are more frequent for the same given time period. For both flow structures, the mixture velocity was a determinant factor, with gas-core slugs dominating the flow at higher velocities. The experimental work led to the modification of existing flow pattern transition models. The modified flow regime maps suggested in this study aim to widen the applicability of the results by enabling the prediction of gas-core slug flow for similar experimental and operating conditions. The present work comprises the initial steps towards automatic flow regime identification in multiphase flow metering. Automatic flow regime recognition has the potential to lead to better process control and improved accuracy in production allocation. •Non-intrusive measurements disclosed slug-like structures with sustained gas-core.•A logic-based algorithm was created for automatic identification of gas-core slugs.•The slippage, time span and frequency of the periodic structures are characterised.•Automatic flow regime identification can lead to improved measurement accuracy.